A new phenanthrene and a new 9, 10-dihydrophenanthren from Bulbophyllum retusiusculum. Issue 20 (18th October 2018) - Sun, Jing; Zhang, Yan; Chen, Lijun; Zhan, Rui; Chen, Yegao
Abstract: A new phenanthrene, bobulretin A (1 ), and a new 9, 10-dihydrophenanthrene, bobulretin B (2 ) along with four known bibenzyls (3 –6 ) were isolated from the whole plants of Bulbophyllum retusiusculum . Their structures were elucidated by means of extensive spectroscopic analysis. Bobulretin B (2 ), isolated as enantiomer mixture with unequal proportions, was verified by analysis on a chiral OD-H HPLC column. Compounds1, 3 and4 were evaluated for their α-glucosidase inhibitory activity. Neither of them showed obvious activity. Abstract :